Striped, bioactive Ce-TiO2 material with peroxynitrite-scavenging activity - Gravina, Noel (2014)
Controlling aligned fiber micro-architectures to simulate the extracellular matrix for inducing important biological functions is a key challenge with regard to successful tissue regeneration. Here we present a bottom-up microemulsion-mediated strategy to obtain highly bioactive and biocompatible, striped Ce–TiO2 nano-crystalline superstructures with ONOO− scavenging activity. The employment of a bulkier organic ceria precursor in the material synthesis has several concurrent effects: (I) influencing the interfacial microemulsion droplet elasticity to create an aligned distribution of prismatic anatase nanoparticles causing the final lined morphology, (II) stabilizing the anatase active phase in a fine dispersed state and improving its resistance to the thermal anatase–rutile conversion, (III) indirectly favoring the rapid formation on the material surface of a hydroxyapatite layer composed of sphere-like globules of 3–5 μm in diameter essential for bone-bonding, and finally (IV) accelerating the ONOO− degradation into less harmful species NO2− and O2.